Hydrodynamic conditioning of diversity and functional traits in subtidal estuarine macrozoobenthic communities. (15th October 2017) - van der Wal, Daphne; Lambert, Gwladys I.; Ysebaert, Tom; Plancke, Yves M.G.; Herman, Peter M.J.
Abstract: Variations in abundance and diversity of estuarine benthic macrofauna are typically described along the salinity gradient. The influence of gradients in water depth, hydrodynamic energy and sediment properties are less well known. We studied how these variables influence the distribution of subtidal macrofauna in the polyhaline zone of a temperate estuary (Westerschelde, SW Netherlands). Macrofauna density, biomass and species richness, combined in a so-called ecological richness, decreased with current velocities and median grain-size and increased with organic carbon of the sediment, in total explaining 39% of the variation. The macrofauna community composition was less well explained by the three environmental variables (approx. 12–15% in total, with current velocity explaining approx. 8%). Salinity, water depth and distance to the intertidal zone had a very limited effect on both ecological richness and the macrofauna community. The proportion of (surface) deposit feeders (including opportunistic species), decreased relative to that of omnivores and carnivores with increasing current velocity and sediment grain-size. In parallel, the proportion of burrowing sessile benthic species decreased relative to that of mobile benthic species that are able to swim. Correspondingly, spatial variations in hydrodynamics yielded distinct hotspots and coldspots in ecological richness. The findings highlight the importance of local hydrodynamic conditions for estuarine restoration and conservation. The study provides a tool based on a hydrodynamic model to assess and predict ecological richness in estuaries. Graphical abstract: Highlights: Richness of subtidal estuarine macrofauna depended on currents and sediment properties. Community composition and functional traits shifted with currents and sediment properties. Salinity, water depth and distance from tidal flats had a minor effect. Hydrodynamic models can predict hotspots and coldspots in ecological richness.